Analisis Performa Load balancing pada Web Server Menggunakan Nginx - Khaidir; Kholik Prasojo; Herlina; A. Muhammad Fuad Fadhlurrahman (PT. Global Research Collaboration, 2025)
The rapid development of information technology, particularly in the use of web-based services, has resulted in increased data traffic to servers. Without proper management, this may lead to decreased system performance. Load balancing is an approach introduced in technology education to teach technical solutions for server load management. This study aims to analyze the impact of implementing load balancing using Nginx software on web server performance. The method applied is a quantitative experiment involving two testing scenarios: before and after the implementation of load balancing using the Round Robin algorithm. The testing environment was built using virtualization with the Ubuntu Server operating system, and performance measurements were conducted using Apache Benchmark and JMeter. The analyzed parameters include latency, throughput, and response time. The findings show that implementing load balancing can significantly improve system efficiency, making it a relevant learning case in computer networking and system administration courses..